An Analysis Of Derivational And Inflectional English Morphemes - Amosi Halawa (Jurnal Ilmiah Langue and Parole, 2017)
derivation and inflection Morpheme is one of the elements present in the field of morphology. Where the morphology is the study of morphemes, and morphemes are elements of language that have the meaning of the free element and bound elements. The problems that exist in this research is to analyze the morpheme of derivation and inflection contained in Jakarta Post. By understanding the derivation and morpheme inflection it can easily develop vocabulary, from one word can gain many meanings This research is a type of research belonging to linguistic field. The research also used qualitative descriptive research method. This research method is a method that refers to the form of words taken from the data source by explaining the intent of data intention. In addition, this research also uses research libraries (library research). This literature research only discusses existing data data by processing and developing data by using morphological theory that supports the research. The first step used by the author is to collect data taken from the source, after that the data are all collected then the writers classify the data in several groups. Since in this study only discusses the three topics of the problem, the first is to classify all types of derivation and morpheme inflection found in the Jakarta Post newspaper, the second is the function of each morpheme, and the last is the rule that belongs to the derivation and morpheme inflection The. Based on this study, the writers found the uniqueness caused by derivation and morpheme inflection when combined with other morphemes. If the morpheme derivation is compared with the free morpheme it will have a different meaning and sometimes even change the word class. While morpheme inflection when compared with free morpheme it will have a grammatical function.